Labour led strategy towards the fourth industrial revolution: a critical appraisal of numsa’s approach to worker control - Ntlokotse, Mamolaba Ruth (University of the Witwatersrand, Johannesburg, 2024)
This research report would not have been possible without the efforts of many people. First, I would like to thank the Almighty God, who bestowed strength throughout the research journey. Embarking on a master’s journey was not easy, especially being a committed trade union leader with many union responsibilities. I am deeply indebted to my Supervisor, Professor Vishwas Satgar; the research report would not have been possible without the support, guidance, and feedback throughout the research project. I cannot begin to express my thanks to comrade Dinga Sikwebu, my mentor and source of inspiration throughout my shop steward journey. His help cannot be overestimated, as he introduced me to worker education and encouraged me throughout my studies. Let it not end with me. I owe a deep sense of gratitude to Professor Michelle Williams for her keen interest in me at every stage of my study. Thank you for being open-minded and constructive throughout. Thank you for giving me a shoulder to lean on when the road was bumpy. Your inspiration, motivation and suggestions have enabled me to complete my research report. I am incredibly grateful to my family who gave me unwavering support: my mom, Amelia; my siblings, Lebohang, Taelo and Thabang; my niece Bokamoso and my nephew, Bophelo. Most importantly, my son Bokang understood the sacrifice I had to make and sometimes did not spend time with him. To my late Dad, Ntate Mosuwe, I know you would be incredibly supportive if you were still alive. Finally, special thanks to everyone who offered invaluable practical contributions to the research project, particularly my comrades from NUMSA in Ekurhuleni. The leadership of SAFTU, especially the General Secretary, Zwelinzima Vavi, and other sister unions, never let me down.
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; 4IR; labour process; union strategy; worker control; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth